Studi Kelayakan Proyek Dalam Relokasi Pasar Kerabut Upaya Meningkatkan Kualitas Layanan - Bela Saputri; Belia Dwi Putri; Sarah Pebrilia; Yonathan Kristiantoro; M. Afdal Samsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the proposed relocation of the Kerabut market to a more strategic location. The relocation of the market is driven by congestion and accident-prone problems that often occur in the previous location due to the lack of good spatial planning. In addition, many traders sell without permits around the market location, thus disturbing the order and cleanliness of the environment. This research uses a descriptive quantitative approach to describe the current condition of the Kerabut market and the potential benefits of relocation. Economic feasibility analysis using the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit/Cost Ratio, and Payback Period methods will be applied to measure the effectiveness of the investment in the new market development. The results of this study are expected to provide comprehensive recommendations regarding the Kerabut market relocation plan, so as to improve efficiency, safety, and convenience for traders.